The Effect of Soaking Liquid Smoke from Coconut Husk Pyrolysis on the Quality of Coir Fish (Selaroides sp.) Smoke Stored at Room Temperature - indra kondihi; Netty Salindeho; Jenky Pongoh; Daisy Makapedua; Nurmeilita Taher; Verly Dotulong (Sam Ratulangi University, 2023)
Fumigation is a method of preservation and processing. Smoked fish products are often found in North Sulawesi. The advantage of smoking fish is to extend the shelf life and provide economic value. Liquid smoke fumigation has several advantages, including reducing the stagnation of PAHs (Polycyclic Aromatic Hydrocarbons), having antioxidant activity, and inhibiting bacterial growth. The purpose of this study was to determine the concentration and duration of immersion in selar fish (Selaroides sp.) liquid smoke solution. The results of this study showed that the best concentration and soaking were 10% liquid smoke with 20 minutes of soaking, which was based on the results of testing the water content ranged from 48.31 – 58.86% at 0 and 3 days of storage, the pH value ranged from 5.16 – 6 .10 at 0 and 3 days of storage, and the total plate number (ALT) ranged from 1.3 x 101 – 4.25 x 102 at 0 days of storage, whereas at 3 days of storage, ALT could not be calculated (TBUD). Keywords: smoke fish, liquid smoke, moisture, pH, TPC Abstrak Pengasapan merupakan salah metode pengawetan dan pengolahan. Produk ikan asap banyak dijumpai di Sulawesi Utara. Keunggulan dari pengasapan ikan adalah memperpanjang massa simpan serta memberikan nilai ekonomis. Pengasapan asap cair mempunyai beberapa keuntungan antara lain dapat mengurangi kandangan senyawa PAH (Polisiklik Aromatik Hidrokarbon), mempunyai aktifitas antioksidan, dan menghambat pertumbuhan bakteri. Tujuan dari penelitian ini adalah untuk menentukan konsentrasi dan lama perendaman dalam larutan asap cair ikan selar (Selaroides sp.). Hasil penelitian ini menunjukkan konsentrasi dan perendaman terbaik yaitu 10% asap cair dengan perendaman 20 menit, yang didasari oleh hasil pengujian kadar air berkisar 48,31 – 58,86% pada penyimpanan 0 dan 3 hari, nilai pH berkisar antara 5,16 – 6,10 pada penyimpanan 0 dan 3 hari, serta angka lempeng total (ALT) berkisar antara 1.3 x 101 – 4.25 x 102 pada penyimpanan 0 hari, sedangkan pada penyimpanan 3 hari ALT tidak bisa untuk dihitung (TBUD). Kata kunci: Ikan asap, asap cair, kadar air, pH, ALT